Profil Oral Hygiene Index–Simplified (OHI‑S) dan Kadar Interleukin‑1β Saliva sebagai Biomarker Inflamasi pada Pasien dengan Gingivitis - Bobby Bobby; Netti Suharti; Nila Kasuma (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Gingivitis represents the initial stage of periodontal disease, primarily induced by dental plaque accumulation and characterized by gingival inflammation. Salivary interleukin-1β (IL-1β) has emerged as a key inflammatory biomarker in periodontal pathology. However, studies specifically examining the association between oral hygiene status and salivary IL-1β levels in adolescents with gingivitis remain limited in the Indonesian population. Objective: This study aimed to describe the Oral Hygiene Index–Simplified (OHI‑S) profile and salivary IL‑1β levels, and to analyze their correlation in adolescent patients with gingivitis. Methods: A cross‑sectional study was conducted involving 36 gingivitis patients aged 15–18 years in Padang City, selected through purposive sampling. Oral hygiene status was assessed using OHI‑S, while unstimulated whole saliva was collected to measure IL‑1β levels via enzyme-linked immunosorbent assay (ELISA). Data were analyzed using univariate and bivariate approaches; Pearson correlation test was applied to evaluate the relationship between OHI‑S and IL‑1β with a significance level set at p<0.05. Results: The mean age of respondents was 15.97±1.03 years, with the majority categorized as middle adolescence (15 years). Only 8.3% of subjects demonstrated good OHI‑S, whereas 66.7% were classified as fair and 25% as poor, indicating substantial plaque and calculus accumulation. A moderate, positive, and statistically significant correlation was observed between OHI‑S scores and salivary IL‑1β levels (r=0.536; p=0.001), suggesting that poorer oral hygiene corresponds to elevated gingival inflammatory activity reflected by increased IL‑1β. Conclusion: Predominantly fair‑to‑poor oral hygiene among adolescents with gingivitis is significantly associated with elevated salivary IL‑1β levels. Salivary IL‑1β demonstrates potential as a non‑invasive inflammatory biomarker that can be integrated with OHI‑S for comprehensive assessment of gingival inflammatory status and for developing targeted preventive strategies against periodontal disease progression in adolescent populations.